Produção de beterraba em função de doses de bokashi e torta de mamona em cobertura - Silva, Priscilla Nátaly de Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
O objetivo deste trabalho foi avaliar a influência de doses de bokashi e torta de mamona aplicados em cobertura na produção de beterraba. Foram realizados quatro experimentos na Fazenda Experimental São Manuel (FCA/UNESP), localizada no município de São Manuel- SP. No primeiro e segundo experimentos foram testadas doses de bokashi em cobertura (0, 150, 300, 450 e 600 g m-2), e uma testemunha com cobertura inorgânica, totalizando seis tratamentos, em delineamento experimental de blocos ao acaso, com quatro repetições. A adubação de plantio constou apenas de composto orgânico (40 t ha-1) no primeiro experimento e no segundo, além do composto orgânico foi feita a adubação inorgânica com NPK 4-14-8 (1,3 t ha-1). No terceiro e quarto experimentos foram testadas doses de torta de mamona em cobertura (0, 150, 300, 450 e 600 g m-2), e uma testemunha com cobertura inorgânica, totalizando seis tratamentos, no delineamento experimental de blocos ao acaso, com quatro repetições. A adubação de plantio constou apenas de composto orgânico (40 t ha-1) no terceiro experimento e no quarto, além do composto orgânico, foi feita a adubação inorgânica com NPK 4-14-8 (1,7 t ha-1). A adubação de cobertura nos experimentos foi parcelada em três vezes, em intervalos de 14 dias após o transplante. As características avaliadas foram: altura...

The objective of this study was to evaluate the influence of doses of Bokashi and castor bean cake applied as coverage in beet production. Four experiments were conducted at the Experimental Farm São Manuel (FCA/UNESP), located in the municipality of San Manuel - SP. In the first and second experiments doses of bokashi were tested (0, 150, 300, 450 and 600 g m-2), totaling six treatments in the experimental design of randomized blocks with four replications. In these experiments (first and second) the planting fertilization consisted only of organic compost (40 t ha-1), and besides the organic compound, it was made inorganic fertilization with NPK 4-14-8 (1,3 t ha-1). In the third and fourth experiments doses of castor bean were tested (0, 150, 300, 450 and 600 g m-2), totaling six treatments, the experimental design of randomized blocks with four replications. In these experiments (third and fourth), the planting fertilization consisted only of organic compost (40 t ha-1) and besides the organic compound, it was made inorganic fertilization with NPK 4-14-8 (1,7 t ha-1). The topdressing in the experiments was divided into three times, at intervals of 14 days after transplantation. The following characteristics were evaluated: plant height, fresh and dry weight of the shoot and the root, root diameter and length, and yield. In the third and fourth experiments, it was also analyzed the accumulation of macronutrients (nitrogen, phosphorus, potassium, calcium, magnesium and sulfur). The application of up to 600 g m-2 of bokashi cover resulted in an increase in plant height, fresh weight of root, root length and beet productivity with and without inorganic fertilizer at planting. The largest contribution to the growth and yield of beet was provided by inorganic topdressing, with little effect of doses of bokashi in coverage. Increases in doses of castor bean cake in coverage provided in all...
Keywords: Beterraba; Adubação orgânica; Nutrientes; Beterraba - Nutriçção; Organic fertilizers